Process of intercalation of C60 with molecular hydrogen from XRD data - Yagotintsev, K.A.; Stetsenko, Yu.E.; Legchenkova, I.V.; Prokhvatilov, A.I.; Strzhemechny, M.A.; Schafler, E.; Zehetbauer, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The process of normal hydrogen infusion into a C60 powder at 1 bar and room temperature was monitored using x-ray diffraction. The effect of the intercalation on the lattice proved to be rather weak: the volume expansion upon complete saturation does not exceed 0.13%. The characteristic saturation time was found to be 320 h; the corresponding diffusion coefficient amounts to (2.8 ± 0.8)·10–14 cm2/s. The integrated reflection intensity calculations for completely saturated sample suggest that only octahedral voids are filled under the conditions of experiment. The effect of complete saturation on the rotational subsystem of the C60 fullerite is rather weak: the orientational phase transition shifts by 6 to 7 K to lower temperatures; no essential hysteresis is noticeable. The dopant shows reluctance to leave the sample under a vacuum of 10–3 Torr at room temperature.